Gas permeability change with deformation and cracking of a sandstone under triaxial compression. Issue 1 (February 2023) - Lin, Yuan-Jian; Liu, Jiang-Feng; Chen, Tao; Huang, Bing-Xiang; Ma, Shi-Jia; Bai, Hai-Bo
No abstract available